The multidimensional development index of new agricultural business entities in mountainous and hilly areas based on the projection pursuit evaluation model: evidence from household survey data in the modern agricultural Park of Jiangjin district, Chongqing - Zhang, Shichao; Zhang, Xuanyun; Liu, Jingyu; Zhang, Xiang; Liu, Yang (Frontiers in Sustainable Food Systems, 2024)
China’s gradual transition from traditional agriculture to modern agriculture has allowed land factors with comparative advantages in the countryside to be identified, which, in turn, has promoted the two-way flow of urban and rural resources, leading to the reallocation of various resources such as land, labor, capital, and technology. Completely realizing the potential of various factors is dependent on forming a beneficial cycle of talent, land, capital, and industry by new business entities. The natural and economic conditions of agricultural resources vary greatly in China, especially in hilly and mountainous areas. Therefore, it is essential to promote the high-quality development of new agricultural businesses in these areas, which will accelerate the construction of modern agricultural management systems and encourage rural revitalization. Furthermore, exploring the multi-dimensional development potential of different types of business entities will stimulate the growth of new agricultural businesses. This study presents a thorough system for evaluating development potential. The system consists of five dimensions: development potential, economic performance, social performance, ecological performance, and development prospects. The projection tracing model is employed to evaluate the development potential of diverse types of business entities. Based on the evaluation results, the development potential of new business entities is categorized according to the village scale in 68 sample villages. The results show the following: (1) The four types of new business entities with the greatest potential for development were agricultural enterprises, followed by farmer cooperatives, and finally large farmers and family farms. From the perspective of industrial types, the agricultural enterprises with the greatest development potential were fruit and vegetable agricultural enterprises; the farmer cooperatives with the greatest development potential were comprehensive farmer cooperatives; the large farmers with the greatest development potential were grain and oil farmers; and the family farms with the greatest development potential were comprehensive family farms. (2) Differences in the dimensions and comprehensive projection values of assorted new business entities were present. The comprehensive projected values in descending order were agricultural enterprises (1.0051), farmer cooperatives (0.8135), large farmers (0.6513), and family farms (0.5972). New corporate entities with distinct potential exhibited variations in high-density locations, showcasing either singular or numerous agglomeration centers. (3) The villages in the study area were divided into five types based on their development potential: low, relatively low, normal, relatively high, and high, accounting for 29.41, 16.18, 27.94, 16.18, and 10.29% of the total villages, respectively. The results of this study demonstrate that, to strengthen the long-term sustainable development capacity of new business entities, it is necessary to recognize the strengths and weaknesses of developing new businesses and promote differentiated growth in various regions.